Topical PDT in the Treatment of Benign Skin Diseases: Principles and New Applications - Kim, Miri (Int J Mol Sci, 2015)
Photodynamic therapy (PDT) uses a photosensitizer, light energy, and molecular oxygen to cause cell damage. Cells exposed to the photosensitizer are susceptible to destruction upon light absorption because excitation of the photosensitizing agents leads to the production of reactive oxygen species and, subsequently, direct cytotoxicity. Using the intrinsic cellular heme biosynthetic pathway, topical PDT selectively targets abnormal cells, while preserving normal surrounding tissues. This selective cytotoxic effect is the basis for the use of PDT in antitumor treatment. Clinically, PDT is a widely used therapeutic regimen for oncologic skin conditions such as actinic keratosis, squamous cell carcinoma in situ, and basal cell carcinoma. PDT has been shown, under certain circumstances, to stimulate the immune system and produce antibacterial, and/or regenerative effects while protecting cell viability. Thus, it may be useful for treating benign skin conditions. An increasing number of studies support the idea that PDT may be effective for treating acne vulgaris and several other inflammatory/infective skin diseases, including psoriasis, rosacea, viral warts, and aging-related changes. This review provides an overview of the clinical investigations of PDT and discusses each of the essential aspects of the sequence: its mechanism of action, common photosensitizers, light sources, and clinical applications in dermatology. Of the numerous clinical trials of PDT in dermatology, this review focuses on those studies that have reported remarkable therapeutic benefits following topical PDT for benign skin conditions such as acne vulgaris, viral warts, and photorejuvenation without causing severe side effects.